Estimation of milk yield gap and factors associated in local cattle of Meghalaya: Application of ANCOVA model - DAS, MRIDUPABAN; SINGH, RAM; FEROZE, SM (The Indian Journal of Animal Sciences, 2021)
The per capita availability of milk in India was 375 g/day in contrast to Meghalaya where the per capita availability was 83 g/per day as of 2017. There exists a huge yield gap in the milk yield in Meghalaya. The study was conducted in the West Khasi Hills and South West Khasi Hills districts of Meghalaya to estimate the milk yield gap and factors associated with it. A sample of 73 respondents was selected and primary data were collected. Standard method for yield gap analysis and ANCOVA model to assess the factors affecting of milk yield gap were employed. Total yield gap (TYG) turned out to be of 244.83% in Meghalaya whereas, 279.75% and 203.03% in West Khasi Hills and South West Khasi Hills districts of Meghalaya, respectively. The total yield gap (TYG) of milk in Meghalaya for local cattle was observed to be much higher as compared to national average. Study revealed that the experience in dairy farming, presence of scientific cattle shed, routine vaccination of cattle, education of household head and human labour allocated for dairy (hours) were significant factors for milk yield gap of local cow in Meghalaya. Hence, these significant factors need due care by individuals of the state who are involved in dairy business. State line department and other institutions like ICAR RC, Barapani and Central Agricultural University (Imphal), Barapani need to intervene through various awareness programmes on scientific dairy management in the state of Meghalaya.